2021
DOI: 10.3390/ijerph18157869
|View full text |Cite
|
Sign up to set email alerts
|

The Lifestyle of Saudi Medical Students

Abstract: This study was conducted to investigate medical students’ lifestyle habits, including sleep quality, eating and drinking patterns, physical activity, and social status. Method: This research project is part two of a multi-institutional cross-sectional observational study conducted among medical students from six medical colleges in Saudi Arabia between September and December 2019. Results: 675 medical students were enrolled electively into the lifestyle study. About half of this number were male students and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…However, that dietary pattern was not in line with our study’s findings, as no association was confirmed between the convenience dietary pattern and academic years, and the mean score for students at year 4 and higher was higher than the mean score of students in their early years at a university [ 17 ]. Several previous studies have demonstrated a higher consumption of fast food among college students [ 34 , 48 , 49 ], but no correlation with academic year has been found. It could be that an increase academic stress in the later years of college lead to an increased consumption of convenience food among senior students.…”
Section: Discussionmentioning
confidence: 90%
“…However, that dietary pattern was not in line with our study’s findings, as no association was confirmed between the convenience dietary pattern and academic years, and the mean score for students at year 4 and higher was higher than the mean score of students in their early years at a university [ 17 ]. Several previous studies have demonstrated a higher consumption of fast food among college students [ 34 , 48 , 49 ], but no correlation with academic year has been found. It could be that an increase academic stress in the later years of college lead to an increased consumption of convenience food among senior students.…”
Section: Discussionmentioning
confidence: 90%
“…Male medical students more often did perform PA up to 30 min and more then 1 h per day in comparison with female medical students, while the female medical students more frequently had PA up to 1 h a day compared to male students. A study by Bin Abdulrahman et al [22] conducted at medical colleges in Saudi Arabia to investigate medical students' lifestyle habits, including PA shows that the greatest number of medical students exhibited healthy lifestyles to some extent. The same study indicates that these health-promoting behaviors differed by medical students' gender, especially when speaking of PA and eating styles [22].…”
Section: Discussionmentioning
confidence: 99%
“…The treatable and preventable mortality rate and the percentage of the population that does not spend time on aerobic PA that improves health (unrelated to work) was higher for the Western Balkans countries compared to European Union average (Table 1) [16][17][18][19]. Global research indicates that only 25-40% of university students are involved in regular PA [20][21][22]. Irregular PA is more common in people of better socioeconomic status, people of rural origin, it is associated with alcohol, tobacco and drug abuse, negative social impact (family, peers, social media, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The favorite leisure activities of medical students in Saudi Arabia are surfing social networks, movies, spending time with friends and family, using the internet (variants identified by us). Only 4.3% of the respondents have more than 30 min of physical activity daily, and women prefer social networks and movies more than men, according to [ 66 ].…”
Section: Discussionmentioning
confidence: 99%